Impact of physical therapy and occupational therapy student placements on productivity: a scoping review - Coleman, Jaimie; Knott, Katey; Jung, Bonny (Canadian Medical Education Journal, 2021)
Introduction: Clinical educators may perceive that student supervision is time consuming and reduces productivity. This perception is in contrast to research conducted in the 1990’s that found students do not negatively impact productivity. There is a need to review the current literature on this topic as a result of health care cost-containment measures that emphasize efficiency. The purpose of this scoping review was to map and examine the impact of physical and occupational therapy student placements on productivity in the clinical environment. Methods: PRISMA Scoping review methodology was used to identify relevant papers. A search was completed in MEDLINE, CINAHL, ERIC and Business Source Premier. Included studies measured clinician productivity while supervising a physical or occupational therapy student. Two reviewers independently reviewed studies according to pre-determined eligibility criteria. Results and discussion: Fourteen studies met the inclusion criteria and were included in the review. Overall, the studies suggest that the supervision of students does not have a negative impact on productivity. However, the productivity measures varied in the type and methods which limits comparisons. This variability, along with the experience of stress by clinical educators as they attempt to satisfy multiple roles may account for the discrepancy between the perception and actual measure of productivity. Conclusions: This scoping review found some evidence that students do not negatively impact productivity. This contrasts with the perception held by the supervising physical and occupational therapists. Further research is recommended to explore this discrepancy and determine optimal productivity measures matched to the characteristics of the environment.